GAMBARAN STATUS GIZI DAN PRODUKTIVITAS KERJA PADA TENAGA KERJA PABRIK PT. SOCFINDO SUNGAI LIPUT ACEH TAMIANG - Gadis Siti Wilda; Evawany Y Aritonang; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Worker nutritional status is one of the important factors that contribute  in supporting workforce productivity. The fulfillment of nutrients will increase a better workforce productivity. This research aims to determine the description of nutrient intakes, workforce productivity and nutritional status of palm oil workers of  PT. Socfindo Sungai Liput Aceh Tamiang. This research is descriptive study with the samples of research about 40 workers in the processing plant. Data collection method is collected by  interviews using employee identity questionnaires, food recall forms and body measurements of workers including weight and height. The results of this research indicate that 65.0% of Socfindo factory workers had normal nutritional status. Workforce productivity of workers is 72,5% productive workers with normal nutritional status 65,4% and workers withnormal hemoglobin level 72,5%. Based on this research, it is recommended to the company of Socfindo palm oil factory especially in the health department to provide guidance to the workers to improve their knowledge about nutrition and do routine health check up related to nutritional status. Keywords: Nutritional Status, Work Productivity